Anatomic maps of erogenous sensation and pleasure in the penis: are there difference between circumcised and uncircumcised men?. (24th January 2023) - Zaliznyak, Michael; Isaacson, Dylan; Duralde, Erin; Gaither, Thomas W; Naser-Tavakolian, Aurash; Bresee, Catherine; Stelmar, Jenna; Yuan, Nance; Topp, Kimberly; Garcia, Maurice M
Abstract: Background: The effects of male circumcision on sexual function remain controversial. Heterogeneity across previous studies and low-quality scientific evidence have resulted in poor understanding of the effects of circumcision on erogenous sensation of the penis and orgasm function. Aim: In this study we sought to describe and assess differences in erogenous genital sensation and reported orgasm function in circumcised compared with uncircumcised men. Methods: Adult male subjects who were recruited on a paid anonymous online survey platform were shown illustrations of 12 anatomic regions of the penis. Subjects were prompted to designate regions as pleasurable when touched during partnered sex and to rate each on a 1-10 scale, with higher erogeneity scores correlating with greater pleasure. Subjects were also asked to characterize their orgasms across 6 experiential domains. Outcomes: Outcomes were differences between circumcised and uncircumcised men in the probabilities that regions would be designated as pleasurable, average pleasure scores, and self-reported orgasm parameters. Results: In total, 227 circumcised (mean [SD] age 46.6 [17.7] years) and 175 uncircumcised men (47.8 [18.1] years) completed the survey. There were no significant differences in average ratings across all regions between circumcised and uncircumcised men. However, significantly more circumcised men reported preferences for the tip of the penis (38% vs 17%, P = .02) and the middle third of the ventral penile shaft (63% vs 48%, P = .04). Additionally, there were no significant differences in orgasm quality and function across all queried domains between circumcised and uncircumcised cohorts. Clinical implications: Our findings suggest that circumcision does not change how men describe erogenous genital sensation or how they experience orgasm. Strengths and limitations: In this study we expanded upon existing literature regarding comparison of sexual function in circumcised and uncircumcised men in its scale and investigation of diverse domains. Limitations include the survey format of data collection. Conclusion: We found no differences in reported erogenous ratings or orgasm function between circumcised and uncircumcised men. These findings suggest that male circumcision does not negatively impact penile erogeneity or orgasm function.